The response of flat slab-column connections of reinforced concrete to high-cycle lateral motion of low amplitude - Dunaiski, Peter Ernst (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D. (Civil Eng.)) -- University of Stellenbosch, 1990.